The Use of TikTok Application to Improve Eleventh-Grade Students’ Speaking Skills - Tiara Z. Koping; Mochtar Marhum; Zarkiani Hasyim; Wahyudin Wahyudin (MASI Mandiri Edukasi, 2025)
This study aimed to investigate the effect of using TikTok’s